Ограничения применения магнитных датчиков виброперемещений - Тонконогий, Владимир Михайлович; Паленный, Юрий Григорьевич; Гугнин, Владимир Павлович; Голобородько, Анна Михайловна (НТУ "ХПИ", 2017)
Рассмотрены проблемы применения магнитных датчиков виброперемещений в связи с ограничениями, связанными с материалом объекта измерений. Определены факторы, влияющие на магнитные свойства сталей. Показаны ограничения метода измерения виброперемещений магнитными датчиками связанные с величиной и вектором напряженности магнитного поля, индукцией насыщения, обратной магнитострикцией, магнитной вязкостью и температурой объекта измерений. Определены меры, которые способствуют снижению влияния перечисленных факторов на погрешность измерений.

The problems of using magnetic sensors for vibrational displacements in connection with the constraints associated with the material of the measurement object were considered. The factors were determined that influencing for: the magnetic properties of steel; the content of carbon and alloying elements; the structure of metals and the heat treatment scheme; the magnitude and vector of the magnetic field intensity; saturation induction, the Villari effect (inverse magnetostriction); the dynamic magnetic permeability and the magnetic viscosity. It is shown that the properties of steel do not change during the measurement, therefore, the influence of the composition of steel and its structure can be taken into account when calibrating the measuring system. In the same way, during of the measurements the dependence of the relative magnetic permeability on the intensity of the magnetic field does not change. It is shown that during measurements the induction caused by the sensor magnet is substantially lower than the induction of saturation of the magnetic field of the measurement object. The effect of reverse magnetostriction for structural and tool steels is negligibly small, and its value does not exceed of the sensitivity of the measuring system used during the measurements. The results of the experimental evaluation of the magnetic viscosity of steel 45 and carbon steel U10 are presented. It is shown that the rotation of the object during the measurements promotes its demagnetization. However, for high-carbon steels, it is advisable to demagnetize the object before taking measurements. It is shown that the magnetic properties of structural steel slightly change when the temperature is raised higher of 400 °C. Conclusions are drawn about the need to calibrate the measuring system when tuning it, demagnetizing the measurement object at the beginning of each measurement cycle, and limiting the temperature of the measurement object no higher than 400 °C.
Application limitations of magnetic vibration sensors
Keywords: измерение магнитными датчиками; ограничения; погрешность измерений; магнитная проницаемость; магнитные свойства сталей; restrictions; measurement error